2018
DOI: 10.3390/ijms19082423
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Sonic Hedgehog in Adult Neurological Diseases: Neurogenesis and Beyond

Abstract: Sonic hedgehog (Shh), a member of the hedgehog (Hh) family, was originally recognized as a morphogen possessing critical characters for neural development during embryogenesis. Recently, however, Shh has emerged as an important modulator in adult neural tissues through different mechanisms such as neurogenesis, anti-oxidation, anti-inflammation, and autophagy. Therefore, Shh may potentially have clinical application in neurodegenerative diseases and brain injuries. In this article, we present some examples, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 180 publications
(225 reference statements)
1
27
0
Order By: Relevance
“…acute seizure models with PTZ versus spontaneous seizures in the pilocarpine model of chronic TLE), which are able to activate different downstream signaling cascades ( Choudhry et al, 2014 ). Moreover, other studies have found that activation of the Shh–Smo signaling pathway increases the synthesis and secretion of neurotrophic factors like nerve growth factor (NGF) and BDNF ( Bond et al, 2013 ; Chen et al, 2018 ; Delmotte et al, 2020 ; Radzikinas et al, 2011 ), which may have neuroprotective effects in TLE ( Bovolenta et al, 2010 ; Falcicchia et al, 2018 ; Paradiso et al, 2009 ). Clearly, additional studies are needed to obtain a deeper knowledge of the cellular and molecular mechanisms linking epilepsy to Shh pathway components.…”
Section: Discussionmentioning
confidence: 99%
“…acute seizure models with PTZ versus spontaneous seizures in the pilocarpine model of chronic TLE), which are able to activate different downstream signaling cascades ( Choudhry et al, 2014 ). Moreover, other studies have found that activation of the Shh–Smo signaling pathway increases the synthesis and secretion of neurotrophic factors like nerve growth factor (NGF) and BDNF ( Bond et al, 2013 ; Chen et al, 2018 ; Delmotte et al, 2020 ; Radzikinas et al, 2011 ), which may have neuroprotective effects in TLE ( Bovolenta et al, 2010 ; Falcicchia et al, 2018 ; Paradiso et al, 2009 ). Clearly, additional studies are needed to obtain a deeper knowledge of the cellular and molecular mechanisms linking epilepsy to Shh pathway components.…”
Section: Discussionmentioning
confidence: 99%
“…Sonic hedgehog (Shh), one of the hedgehog (Hh) family members, was initially identified as a morphogen critically involved in neural development during embryogenesis. In addition to being implicated in neural development, Shh also appears as a vital modulator in adult neural tissues by diverse mechanisms such as anti-inflammation, antioxidation, autophagy, and neurogenesis [ 84 ]. Hence, Shh may possibly possess clinical significance in neurodegenerative diseases.…”
Section: Id1 and Ad-a Roles In Cell Cycle Reentry And Cell Deathmentioning
confidence: 99%
“…To our knowledge, this study provides the first hints for the hypothesis that the human GAN pathology has a neurodevelopmental component, but it also opens an exciting new avenue for a role of the Shh pathway in adulthood. Indeed, in the mammalian adult brain, Shh signaling has emerged as an important neuromodulator through different mechanisms, including the proliferation of postnatal neural stem cells and fate specification (60,61). One could therefore speculate for the human pathology, that the gigaxonin-mediated Shh repression can act at multiple levels in prenatal and postnatal stages.…”
Section: Number 12 December 2019mentioning
confidence: 99%
“…Since GAN is an early-onset pathology, a more comprehensive study aimed at deciphering the control of Shh signaling by gigaxonin during development and in adulthood could shed light on possible treatment windows for this yet incurable and fatal disease. In light of the therapeutic benefits obtained by modulating the Shh pathway in several neurodegenerative conditions (60), our study may also offer a specific target for therapeutic intervention aimed at reactivating neurogenesis in disease.…”
Section: Number 12 December 2019mentioning
confidence: 99%